2015
DOI: 10.1155/2015/934195
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Static Magnetic Fields on the Physical, Mechanical, and Microstructural Properties of Cement Pastes

Abstract: This paper presents the results of an experimental study carried out to comprehend the physical, mechanical, and microstructural behavior of cement pastes subjected to static magnetic fields while hydrating and setting. The experimental methodology consisted in exposing fresh cement pastes to static magnetic fields at three different magnetic induction strengths: 19.07, 22.22, and 25.37 Gauss. The microstructural characterization makes evident that there are differences in relation to amount and morphology of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 26 publications
2
12
1
1
Order By: Relevance
“…On the other hand, the authors conclude that the magnetic field does not seem to have a noticeable effect on the morphology and formation of early age hydration product, and does not influence the final compressive strength. This seems to be in contradiction with the previously mentioned conclusions obtained by Soto-Bernal et al [ 38 ], showing that further research is needed to elucidate the effect of magnetic fields on cement hydration and microstructure development. Disregarding the discussion on the effect of magnetic field on hydration, the research of Nair and Ferron [ 39 ] is a major step forward towards active rheology control of cementitious materials.…”
Section: Current Practices With Active Intervention To Control Concrecontrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the authors conclude that the magnetic field does not seem to have a noticeable effect on the morphology and formation of early age hydration product, and does not influence the final compressive strength. This seems to be in contradiction with the previously mentioned conclusions obtained by Soto-Bernal et al [ 38 ], showing that further research is needed to elucidate the effect of magnetic fields on cement hydration and microstructure development. Disregarding the discussion on the effect of magnetic field on hydration, the research of Nair and Ferron [ 39 ] is a major step forward towards active rheology control of cementitious materials.…”
Section: Current Practices With Active Intervention To Control Concrecontrasting
confidence: 99%
“…Soto-Bernal et al [ 38 ] studied the effect of maintained static magnetic fields applied during hardening on the performance of cement paste. They concluded that more CSH is produced, with denser morphology and reduced porosity.…”
Section: Current Practices With Active Intervention To Control Concrementioning
confidence: 99%
“…In addition to cryogenic treatment, scholars magnetize material with ferromagnetism to enhance the material property [13][14][15][16]. ere are two ways to apply magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…They also found that the water temperature increased due to the use of MW. They also established a direct relationship between the density of the magnetic field and the time of cement setting [20]. Wei et al [21] showed that the water magnetized into the concrete decreased shrinkage.…”
Section: Introductionmentioning
confidence: 97%
“…Soto-Bernal et al [20] used scanning electron microscopy(SEM) tests to demonstrate the increase of magnetic field effects in denser moist C-S-H gels, which in turn increased the compressive strength in the concrete and mortar. They also found that the water temperature increased due to the use of MW.…”
Section: Introductionmentioning
confidence: 99%